PSMA-targeted low-molecular double conjugates for diagnostics and therapy - Petrov, Stanislav A.; Zyk, Nikolay Y.; Machulkin, Aleksei E.; Beloglazkina, Elena K.; Majouga, Alexander G. (European journal of medicinal chemistry, 2021)
This review presents data on dual conjugates of therapeutic and diagnostic action for targeted delivery to prostate cancer cells. The works of the last ten years on this topic were analyzed. The mail attention focuses on low-molecular-weight conjugates directed to the prostate-specific membrane antigen (PSMA); the comparison of high and low molecular weight PSMA-targeted conjugates was made. The considered conjugates were divided in the review into two main classes: diagnostic bimodal conjugates (which are containing two fragments for different types of diagnostics), theranostic conjugates (containing both therapeutic and diagnostic agents); also bimodal high molecular weight therapeutic conjugates containing two therapeutic agents are briefly discussed. The data of in vitro and in vivo studies for PSMA-targeted double conjugates available by the beginning of 2021 have been analyzed. [Display omitted] •50 LMW PSMA-targeted bimodal diagnostic or theranostic conjugates are described.•These conjugates are available, have high tissue penetration and fast pharmacokinetic.•Synthesis with Lys-like amino acids as a branch point is preferable for such conjugates.•Different radio and fluorescent label dosages at diagnostic conjugates is the problem.•Double diagnostic conjugates are most advanced for implementation in medicine.